Rancang Bangun Alat Konversi Limbah Plastik Menjadi Bahan Bakar Melalui Pirolisis - Indah Pratiwi (Universitas Dehasen Bengkulu, 2022)
Plastic is a type of waste which is very difficult to degrade. It takes thousands of years to decompose plastic waste by the soil, and when it decomposes it will pollute the soil and groundwater. One way to reduce plastic waste is by pyrolysis. The temperature needed to pyrolyze plastics is from 200 0C up to 300 0C, so it takes a lot of energy to pyrolyze plastics. This study aims to design a plastic pyrolysis device. The design was done after technical analysis conducted on the tool, where the yield value was calculated in the plastic pyrolysis tool. This research produces product in form of pyrolysis oil. From the results of the tests carried out on the plastic-pyrolysis tool, the yield value of each product was 1.85%. The capacity of this plastic pyrolysis tool was 11.3 ml/hour.